Radiotherapy for localized gastric mucosa–associated lymphoid tissue lymphoma: long-term outcomes over 10 years. (11th January 2017) - Ohkubo, Yu; Saito, Yoshihiro; Ushijima, Hiroki; Onishi, Masahiro; Kazumoto, Tomoko; Saitoh, Jun-ichi; Kubota, Nobuko; Kobayashi, Hirofumi; Maseki, Nobuo; Nishimura, Yu; Kurosumi, Masafumi
Abstract: This study aimed to assess the long-term outcomes of radiotherapy in patients with localized gastric mucosa–associated lymphoid tissue (MALT) lymphoma. Twenty-seven patients with Stage I gastric MALT lymphoma were treated with radiotherapy from 1999 to 2010. The median age was 65 years (range: 31–84). Fifteen patients were Helicobacter pylori –negative. Thirteen patients were treated with definitive radiotherapy alone. The other 14 patients who had refractory or residual disease following a prior treatment received salvage radiotherapy. The median dose of the radiotherapy was 30 Gy in 20 fractions (range: 30–39.5 Gy). The median follow-up period was 121 months (range: 8–176 months). The 5- and 10-year overall survival rates for all patients were 92% and 87%, respectively. No patients died from MALT lymphoma. Three patients died of other diseases at 8, 33 and 74 months after radiotherapy (myocardial infarction, pneumonia and hepatocellular carcinoma, respectively). No cases of local recurrence were observed during the follow-up period. There were no serious late gastric, liver or kidney complications during a median follow-up period of over 10 years. Two patients remain alive with distant metastases: a lung metastasis and an abdominal lymph node metastasis at 104 months and 21 months after radiotherapy, respectively. Excellent long-term local control was observed in patients with localized gastric MALT lymphoma after radiotherapy. However, lifelong follow-up should be conducted to detect cases of late recurrence, especially distant metastases.